Islamic Banking Efficiency: Comparative Studies Between Malaysia and Indonesia - Ika Yulita; Sofyan Rizal (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2016)
The purpose of this research is to measure efficiency level of sharia banking in Malysia and Indonesia countries and to analyze the factors affecting the level of efficiency of sharia banking for both countries. This reseach uses DEA (Data Envelopment Analysis) method in order to test the assumptions of Variabel Return to Scale (VRS), and uses Kolmogorov-Smirnov and Mann Whitney U-Test in order to test normality, and uses regression dummy variable of the data from the first quarter of 2011 until the fourth quarter of 2014. The research shows overall level of efficiency of sharia banking in Malaysia and Indonesia countries are fluctuating. Based on result, sharia banking in Indonesia more efficient than sharia banking in Malaysia; However, there is no significant differences among them. The reasons of this inefficiency are deposits, total financing, fixed asset, and personnel cost. However, operational income is the most efficient variabel for both countriesDOI: 10.15408/sjie.v5i1.3129